Impact of earthing system designs and soil characteristics on tower footing impedance and ground potential rise: A modelling approach for sustainable power operation - Nasir N.A.F.M.; Kadir M.Z.A.A.; Osman M.; Rahman M.S.A.; Amirulddin U.A.U.; Nasir M.S.M.; Zaini N.H.; Ali N.H.N. (MDPI AG, 2023)
footing; lightning; modeling; operations technology; parameter estimation; soil structure; sustainability; Malaysia